Microwave-assisted solvothermal synthesis of hollow mesoporous SiOC ceramics in NaOH solution. Issue 13 (1st July 2022) - Xia, Kedong; Liu, Xiao; Liu, He; Li, Weichen; Li, Yuwei; Han, Fang; Duan, Lingyao; Hou, Zhenyu
Abstract: Hollow SiOC ceramics were prepared by a microwave-assisted solvothermal method, and only mesopores were formed in NaOH solution. Increasing the microwave temperature and NaOH concentration not only increased the oxygen-enriched units and reduced the Si–C bonds of precursors, but also enhanced the etching effect in the interior SiOC ceramics. The specific surface area of SiOC ceramics increased with increasing solvothermal temperature and decreased with increasing NaOH concentration. In addition, the effect of synthesis temperature on the formation of hollow SiOC ceramics is more significant than that of NaOH concentration. Although the free C content is reduced, the microwave solvothermal synthesis results in the formation of graphitic C in SiOC ceramics. The surface CO is formed at the cost of some C–OH as the microwave temperature increases, which increases the amorphous C content of SiOC ceramics.